2005
DOI: 10.1007/bf03015771
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac analgesia for inguinal hernia repair is not improved by peripheral administration

Abstract: Adding ketorolac to lidocaine infiltration for hernia repair does not improve or prolong postoperative analgesia compared to systemic administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…These results are consistent with a previous report in rats, where local infiltration of ketorolac in combination with dexamethasone reduced postoperative pain scores only until 2 h after laparotomy, which could be attributed to the systemic absorption of drugs provided by the large vascularization of the abdominal cavity [22]. In human surgical patients undergoing hernia repair, no significant analgesic benefits were found with local infiltration of NSAIDs compared to systemic injection of meloxicam [18] or ketorolac [23]. Moreover, some aspects of our experimental protocol may have contributed to the apparent lack of a prolonged postoperative analgesic effect of ropivacaine in combination with meloxicam.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with a previous report in rats, where local infiltration of ketorolac in combination with dexamethasone reduced postoperative pain scores only until 2 h after laparotomy, which could be attributed to the systemic absorption of drugs provided by the large vascularization of the abdominal cavity [22]. In human surgical patients undergoing hernia repair, no significant analgesic benefits were found with local infiltration of NSAIDs compared to systemic injection of meloxicam [18] or ketorolac [23]. Moreover, some aspects of our experimental protocol may have contributed to the apparent lack of a prolonged postoperative analgesic effect of ropivacaine in combination with meloxicam.…”
Section: Discussionsupporting
confidence: 92%
“…Six studies evaluated the effects of conventional NSAIDs (tenoxicam, meloxicam) ( Table 3 )17, 19, 69–72. Overall, there was no difference in pain scores at rest or on movement, need for supplementary analgesics, and time to first analgesic request.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…In pain management after elective caesarean delivery, Lavand'homme et al in 2007 showed that continuous intra‐wound infusion with diclofenac offered better pain control, without adverse effect as compared with the same dose administered systemically by intermittent intravenous injection [31]. None of the patient in the study had significant post‐operative bleeding [31, 33, 34] or wound infection [4, 31, 33] and delay wound healing [4, 31]. Despite these findings, NSAID wound infiltration has not been included in many peri‐operative analgesic guidelines although generic NSAIDs are cheap and readily available especially in the middle and low‐resourced surgical settings.…”
Section: Introductionmentioning
confidence: 99%